Achievement Motivation and Employee Commitment: The Role of Leadership - Bob Foster (Kontigensi : Jurnal Ilmiah Manajemen, 2020)
It can not be denied that the role of leaders in improving organizational progress. This has been confirmed by previous researchers. This study aims to determine the effect of leadership function in increasing the motivation and commitment of employees in one agency in Bandung. Sample taken from one of the government agencies in the city of Bandung that serve the problem of tourism. Quantitative approach is done in answering the objectives of the study. The results support previous research that leadership functions have a significant effect on employee motivation and commitment. This shows that the role of leaders in improving employee motivation and commitment plays an important role in the organization in order to achieve organizational goals that have been established.